Zagrożenia środowiska przyrodniczego pasma Odry = The menaces of natural environment in the strip of Odra River - Wira, Jerzy; Ryter-Przybylska, Zofia; Kowalski, Piotr; Urban, Jerzy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The problem of menace of natural environment in the Valley of Odra River was presented in the paper. The described menaces were divided into two groups: naturegenic - caused by changes in the nature and anthropogenic - connected with human activity.
Keywords: Odra; zagrożenia naturogeniczne; zagrożenia atropogeniczne